A Content Analysis of Women’s Experiences of Workplace Bullying Since 2000 - Mitsunori Misawa; Josie L Andrews; Kathy Mae Jenkins (Adult Education Research Conference, 2018)
A content analysis was conducted to explore women’s experiences of bullying in the workplace, which revealed characteristics, impacts, and strategies of women being bullied at work.
Keywords: workplace bullying; women; content analysis